Economic impact of switching from partially combined vaccine "Pentaxim® and hepatitis B" to fully combined vaccine "Hexaxim®" in the Malaysian National Immunization Program - Syed Mohamed Aljunid; Lama Al Bashir; Aniza Binti Ismail; Azimatun Noor Aizuddin; S. A. Zafirah Abdul Rashid; Amrizal Muhammad Nur (BMC, 2022)
Abstract Background The decision to implement new vaccines should be supported by public health and economic evaluations. Therefore, this study was primarily designed to evaluate the economic impact of switching from partially combined vaccine (Pentaxim® plus hepatitis B) to fully combined vaccine (Hexaxim®) in the Malaysian National Immunization Program (NIP) and to investigate healthcare professionals (HCPs)' and parents'/caregivers' perceptions. Methods In this economic evaluation study, 22 primary healthcare centers were randomly selected in Malaysia between December 2019 and July 2020. The baseline immunization schedule includes switching from Pentaxim® (four doses) and hepatitis B (three doses) to Hexaxim® (four doses), whereas the alternative scheme includes switching from Pentaxim® (four doses) and hepatitis B (three doses) to Hexaxim® (four doses) and hepatitis B (one dose) administered at birth. Direct medical costs were extracted using a costing questionnaire and an observational time and motion chart. Direct non-medical (cost for transportation) and indirect costs (loss of productivity) were derived from parents'/caregivers' questionnaire. Also, HCPs' and parent's/caregivers' perceptions were investigated using structured questionnaires. Results The cost per dose of Pentaxim® plus hepatitis B vs. Hexaxim® for the baseline scheme was Malaysian ringgit (RM) 31.90 (7.7 United States dollar [USD]) vs. 17.10 (4.1 USD) for direct medical cost, RM 54.40 (13.1 USD) vs. RM 27.20 (6.6 USD) for direct non-medical cost, RM 221.33 (53.3 USD) vs. RM 110.66 (26.7 USD) for indirect cost, and RM 307.63 (74.2 USD) vs. RM 155.00 (37.4 USD) for societal (total) cost. A similar trend was observed for the alternative scheme. Compared with Pentaxim® plus hepatitis B, total cost savings per dose of Hexaxim® were RM 137.20 (33.1 USD) and RM 104.70 (25.2 USD) in the baseline and alternative scheme, respectively. Eighty-four percent of physicians and 95% of nurses supported the use of Hexaxim® in the NIP. The majority of parents/caregivers had a positive perception regarding Hexaxim® vaccine in various aspects. Conclusions Incorporation of Hexaxim® within Malaysian NIP is highly recommended because the use of Hexaxim® has demonstrated substantial direct and indirect cost savings for healthcare providers and parents/caregivers with a high percentage of positive perceptions, compared with Pentaxim® plus hepatitis B. Trial registration Not applicable.